Preferred Materials and Methods Employed for Endodontic Treatment by Iranian General Practitioners - Raoof, Maryam; Zeini, Negar; Haghani, Jahangir; Sadr, Saeedeh; Mohammaalizadeh, Sakineh (Iranian Endodontic Journal, 2015)
Introduction: The aim of this study was to gather information on the materials and methods employed in root canal treatment (RCT) by general dental practitioners (GDPs) in Iran. Methods and Materials: A questionnaire was distributed among 450 dentists who attended the 53th Iranian Dental Association congress. Participants were asked to consider demographic variables and answer the questions regarding the materials and methods commonly used in RCT. Descriptive statistics were given as absolute frequencies and valid percentages. The chi-square test was used to investigate the influence of gender and the years of professional activity for the employed materials and techniques. Results: The response rate was 84.88%. The results showed that 61.5% of the participants did not perform pulp sensitivity tests prior to RCT. Less than half of the general dental practitioners (47.4%) said that they would trace a sinus tract before starting the treatment. Nearly 16% of practitioners preferred the rubber dam isolation method. Over 36% of the practitioners reported using formocresol for pulpotomy. The combined approach of working length (WL) radiographs and electronic apex locators was used by 35.2% of the practitioners. Most of the respondents used K-file hand instruments for canal preparation and the technique of choice was step-back (43.5%), while 40.1% of respondents used NiTi rotary files, mostly ProTaper and RaCe. The most widely used irrigant was normal saline (61.8%). Calcium hydroxide was the most commonly used inter appointment medicament (84.6%). The most popular obturation technique was cold lateral condensation (81.7%) with 51% using zinc oxide eugenol-based sealers. Conclusions: The majority of Iranian GDPs who participated in the present survey do not comply with quality guidelines of endodontic treatment.